Global diversity of the Ganoderma lucidum complex (Ganodermataceae, Polyporales) inferred from morphology and multilocus phylogeny - Zhou, Li-Wei; Cao, Yun; Wu, Sheng-Hua; Vlasák, Josef; Li, De-Wei; Li, Meng-Jie; Dai, Yu-Cheng (Phytochemistry, 2015)
Species of the Ganoderma lucidum complex are used in many types of health products. However, the taxonomy of this complex has long been chaotic, thus limiting its uses. In the present study, 32 collections of the complex from Asia, Europe and North America were analyzed from both morphological and molecular phylogenetic perspectives. The combined dataset, including an outgroup, comprised 33 ITS, 24 tef1α, 24 rpb1 and 21 rpb2 sequences, of which 19 ITS, 20 tef1α, 20 rpb1 and 17 rpb2 sequences were newly generated. A total of 13 species of the complex were recovered in the multilocus phylogeny. These 13 species were not strongly supported as a single monophyletic lineage, and were further grouped into three lineages that cannot be defined by their geographic distributions. Clade A comprised Ganoderma curtisii, Ganoderma flexipes, Ganoderma lingzhi, Ganoderma multipileum, Ganoderma resinaceum, Ganoderma sessile, Ganoderma sichuanense and Ganoderma tropicum, Clade B comprised G. lucidum, Ganoderma oregonense and Ganoderma tsugae, and Clade C comprised Ganoderma boninense and Ganoderma zonatum. A dichotomous key to the 13 species is provided, and their key morphological characters from context, pores, cuticle cells and basidiospores are presented in a table. The taxonomic positions of these species are briefly discussed. Noteworthy, the epitypification of G. sichuanense is rejected.
Keywords: tef1α; North America; Phylogeny; Ganoderma; rpb2; rpb1; Evropa; Europe; Polyporales; Plants, Medicinal; Polypore; ITS; Taxonomy; léčivé rostliny; fylogeneze; Severní Amerika